The sequence determinants of amyloid fibril formation - Chiti, Fabrizio (Henry Stewart Talks, 2007)
Amyloid fibril formation is a shared property of proteins, The effect of mutations on the aggregation of unstructured polypeptide chains, The importance of hydrophobicity, propensity to form beta-sheet structure and charge in amyloid formation of unstructured proteins, The regions of the sequence forming the beta-core of amyloid fibrils, The sequence and structural determinants of aggregation for partially folded states of proteins, Amino acid sequences have evolved to avoid formation of amyloid-like aggregates
Archived at 2021/02/25